2018
DOI: 10.1002/iub.1755
|View full text |Cite
|
Sign up to set email alerts
|

USP4 expression independently predicts favorable survival in lung adenocarcinoma

Abstract: Ubiquitin specific protease 4 (USP4) is a member of the USPs family, which catalyzes the cleavage of ubiquitin from a series of protein substrates, thereby modulating a number of cellular signaling pathways. In this study, we aimed to explore the expression profile of USP4 in lung adenocarcinoma (LUAD) using large patient cohorts in the Cancer Genome Atlas and the International Cancer Genome Consortium and to investigate its prognostic value and the possible mechanisms of its dysregulation. Results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In line with these results, a protective effect of USP4 was reported in lung adenocarcinoma and breast cancer patients, although distinct effects of USP4 have been reported for other cancer types [48][49][50][51][52][53]. For instance, expression of USP4 was downregulated in lung adenocarcinoma, and low USP4 expression was associated with poor overall survival and recurrence-free survival [48]. Expression of USP4 was also significantly reduced in breast cancer tissue.…”
Section: Discussionsupporting
confidence: 63%
“…In line with these results, a protective effect of USP4 was reported in lung adenocarcinoma and breast cancer patients, although distinct effects of USP4 have been reported for other cancer types [48][49][50][51][52][53]. For instance, expression of USP4 was downregulated in lung adenocarcinoma, and low USP4 expression was associated with poor overall survival and recurrence-free survival [48]. Expression of USP4 was also significantly reduced in breast cancer tissue.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have shown that USP4 expression was significantly decreased in breast cancer tissue and that USP4 inhibited breast cancer cell growth through inhibiting PDCD4 degradation 41 . USP4 was downregulated in lung adenocarcinoma and served as an independent predictor 42 . Some other studies claimed that USP4 might have oncogenic properties.…”
Section: Discussionmentioning
confidence: 97%
“…Yao R et al suggested that esophageal cancer patients with high USP4 expression had relative longer survival time [43]. Some researchers also concluded that USP4 expression might be a favorable biomarker for OS and RFS in LUAD patients, while it was worth noting that USP4 expression has no prognostic value for OS and RFS in lung squamous cell carcinoma [44]. In addition, Ye et al suggested that USP4 had anti-cancer effect in breast cancer, and found that USP4 could inhibited the growth of tumors in a mouse tumor xenograft model [45].…”
Section: Discussionmentioning
confidence: 99%